Studies on foetal fluids in goats - Bongso, Tuan Ariffeen; Edirisinghe, R.; Athuraliya, D. (Indian Veterinary Association, 1979)

(untitled)
Throughout gestation, the ruminant foetus is enclosed by two foetal sacs containing fluid, viz, an inner amniotic sac containing amniotic fluid and an outer allantoic sac containing allantoic fluid. The human foetus however is enclosed by a single amniotic sac containing amniotic fluid. These fluids have an important physiological role to pJay during pregnancy as well as causing distension of the uterus, thereby making pregnancy diagnosis possible both by rectal palpation and external ballotment. Further, the foetal fluids help cervical dilatation and easy passage of the foetus through the birth canal at parturition. In certain pathological conditions in cattle, sheep and goats such as mummification and dropsy of the foetal membranes, the volumes of these fluids may be decreased or increased (Roberts. 1971). Hence, information on the normal volumes of these fluids with gestation in these species is needed in order to recognise such pathological conditions. Detailed studies on the normal foetal fluid volumes have been reported for man (Fuchs 1966; Queenan et al., 1972; Haswell and Morris 1973), cattle (Arthur 1957. Bongso and Basrur 1976), sheep, horses, pigs and cats (Arthur 1969). There are only two reports on such volume studies in .the goat (Richter and Gotze 1960; Lyngset 1971) and even in these studies the numbers of samples investigated have been small. This study was thus undertaken to shed more light on this aspect in the goat and furnish detailed information on colour, consistency and volumes of foetal fluid throughout the gestation period on a larger number of samples.